2000
DOI: 10.1002/1097-4628(20001213)78:12<2134::aid-app80>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Decabromobiphenyl oxide-aluminum hydroxide system as a flame retardant for styrene-butadiene rubber

Abstract: Styrene–butadiene rubber (SBR) was treated with decabromobiphenyl oxide (DBBO) and/or aluminum hydroxide [Al(OH)3] as a flame retardant. The flammability of the resulting system was determined by the limiting oxygen index method. The effect of the added flame retardants on the maximum torque (MH), curing rate, and tensile properties was also evaluated. The results showed, particularly, that DBBO was a more effective flame retardant than was Al(OH)3. On the other hand, this brominated compound reduced the modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…M. A. Khattab suggested that the use of combined flame retardant consist of PBPE and Al(OH) 3 lead to the decrease of flame retardancy of rubber materials 18. He also reported that this combined system appears as a high performance for cellulose and other thermoplastic polymer 18. In our study, the synergic effect of combined flame retardant is observed in formulation up to 10 wt % of each flame retardant.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…M. A. Khattab suggested that the use of combined flame retardant consist of PBPE and Al(OH) 3 lead to the decrease of flame retardancy of rubber materials 18. He also reported that this combined system appears as a high performance for cellulose and other thermoplastic polymer 18. In our study, the synergic effect of combined flame retardant is observed in formulation up to 10 wt % of each flame retardant.…”
Section: Resultssupporting
confidence: 63%
“…UL‐94 test results of acrylic PSA with combined flame retardant are collected from Table VI to VIII. M. A. Khattab suggested that the use of combined flame retardant consist of PBPE and Al(OH) 3 lead to the decrease of flame retardancy of rubber materials 18. He also reported that this combined system appears as a high performance for cellulose and other thermoplastic polymer 18.…”
Section: Resultsmentioning
confidence: 99%
“…However, ATH has an essential disadvantage, that a greater than 60% ATH loading is required to meet flame‐retardant properties; this could be detrimental to the mechanical properties of flame‐retardant materials. Many investigations have been done on ATH incorporated with other halogen‐free flame‐retardant synergistic agents2–10 to enhance flame resistance and decrease the high loading level of ATH. Ramazani et al3 reported the synergistic effect of zinc borate with ATH in the flame retardance and physicomechanical properties of propylene composites.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have been carried out on ATH incorporated with other halogen free flame retardant synergistic agents to enhance the flame resistance and decrease the high loading level of ATH. [5][6][7][8][9][10][11] Red phosphorus (RP) is one of the ecologically and physically most harmless alternative fire retardants, 12 since encapsulation and use of master batches have been established successfully to eliminate problems of handling safety and stability. In addition, it has been reported that RP can be used as a synergistic agent with hydrated fillers, such as AI(OH) 3 and Mg(OH) 2 in plastics.…”
Section: Introductionmentioning
confidence: 99%